2016
DOI: 10.1111/jog.13066
|View full text |Cite
|
Sign up to set email alerts
|

Rectovaginal fistula: Twenty years of rectovaginal repair

Abstract: Age, education level and ability to pay insurance significantly affect 12-month outcome of RVF. Surgery is the preferred option, while medical treatment should be used only for small rectovaginal fistulas or for patients not suitable for surgery and anesthesia. More support and assistance should be offered to those patients with unfavorable factors, such as old age, low education level and inability to afford insurance. All RVF secondary to obstetrical injury had a 100% favorable outcome compared with those se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
0
15
1
1
Order By: Relevance
“…In our study, the proportion of RVF etiology was quite different from that of previous reports [5, 7, 15, 16]. Congenital malformation, obstetric injury, and iatrogenic cause represented the majority (85%)of cases in our study, whereas inflammatory bowel disease is the leading cause of RVF in the literature [5, 7].…”
Section: Discussioncontrasting
confidence: 92%
“…In our study, the proportion of RVF etiology was quite different from that of previous reports [5, 7, 15, 16]. Congenital malformation, obstetric injury, and iatrogenic cause represented the majority (85%)of cases in our study, whereas inflammatory bowel disease is the leading cause of RVF in the literature [5, 7].…”
Section: Discussioncontrasting
confidence: 92%
“…A variety of methods and materials have been reported for vaginal repair and RVF treatment [ 12 , 24 – 26 ]. Early intervention including supplementary diverting stoma can improve the success rate of RVF healing [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no standard or widely accepted treatment for RVF [ 10 , 11 ]. Patients who received surgical treatment are generally considered to have a better prognosis compared with those receiving conservative treatment [ 12 ]. However, whether transverse colostomy is superior to ileostomy to repair RVF, whether rectovaginal fistula need to be repaired, and what the optimal time is for stoma closure are still controversial and warrant further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…30 Lo et al found that 64% of RVF patients treated nonoperatively had improvement in their symptoms at 12 months, but this was less than the 89% who had improvement at 12 months after surgery. 31 In addition to medical management, there are options for limited repair. Fibrin glue injection has definitive closure rates in the 10 to 15% range, and thus is typically reserved for patients who cannot tolerate more invasive procedures.…”
Section: Conservative Managementmentioning
confidence: 99%